THE EFFECT OF RECIPROCAL TEACHING LEARNING MODEL ON THE STUDENTS LEARNING OUTCOMES OF CLASS XI TBSM B ON THE SUBJECT OF REPARATION OF ELECTRICAL IGNITION SYSTEM AT KAHAYAN HILIR 1 STATE VOCATIONAL SCHOOL AT ACADEMIC YEAR 2017/2018 - Febrianto Saputra; Debora (Jurusan Pendidikan Teknologi Dan Kejuruan, 2020)
This study aims to determine the effect of the influence in using reciprocal teaching model on the learning outcomes of students in class XI TBSM for the subject of reparation of electrical ignition system in SMKN-1 Kahayan at academic year 2017/2018. This study applies the Quasi Experimental Design method with a research design based on True Experimental Design Type for Pretest-Posttest Control Group model. The population samples are consisting of throughout students in Class XI TBSM B as an Experiment class and class XI TBSM A as a control class. Moreover, data collection was carried out using several tests, which consisted of pretest and posttest. The collected data was then analyzed statistically using the average pre-test, post-test and two-mean differences. Based on the results of pretest data analysis, the average value of the experimental class and the control class are respectively contributing at about 60.89 and 60.52. Meanwhile, the post-test values for both the experimental class and the control class are on 81.50 and 74.56. The calculation of the two average for experimental and control classes provide the percentage of 5% as significant level that obtained the value of ttable = 1.685 and tcount = 5.17. When thitung 5.17 > ttabe 1.685, H0 is rejected and H1 is accepted. Therefore the results of these studies it can be concluded that there is an influence of student learning outcomes in the experimental class using the Reciprocal Teaching learning model.